Allergenic Fungal Spores, Climate Change, Urbanization, and Socioeconomic Disparities in Lithuania: A Non-Systematic Literature Review - Halak, Karamello (Slauga. Mokslas ir praktika, 2025)
Socioeconomic inequality, urbanization, and climate change significantly impact environmental allergen dispersion and health outcomes. Despite global evidence, research on allergenic fungal spores in Lithuania remains limited. This study aims to explore the influence of urbanization, socioeconomic inequality, and climate change on allergenic fungal spore exposure and allergy risk in Lithuania, identifying knowledge gaps and proposing preventive strategies. A comprehensive narrative literature review was conducted, integrating case studies, observational and experimental research, clinical reports, and comparative international data. The results highlight that allergenic fungal spores, particularly Alternaria and Cladosporium, substantially impact respiratory health. Climate change is projected to extend spore seasons and intensify allergen exposure. Urban settings are associated with increased indoor fungal exposure, especially affecting low-income populations. Socioeconomic factors exacerbate health disparities due to inadequate housing conditions and limited access to healthcare. In conclusion, climate change, urbanization, and socioeconomic disparities collectively amplify the risks posed by allergenic fungal spores in Lithuania. Targeted interventions and comprehensive public health policies are necessary to mitigate the rising allergy burden.